2020
DOI: 10.18231/j.ijced.2020.056
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of efficacy and safety of fractional CO2 laser and microneedling fractional radiofrequency (MnRF) in the treatment of striae distensae

Abstract: Striae Distensae (SD) are common disfiguring skin conditions having significant psychological impact on affected patients, especially in young healthy women. Management of striae poses a therapeutic challenge. Recently, fractional CO2 laser and microneedling radio frequency have shown to be efficacious in the treatment of SD. However, there is paucity of such studies in Indian population. Hence, we intend to conduct the present comparative study. To compare the efficacy and safety of fractional CO2 laser and M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…17 Gosh et al also showed than 73.3% subjects with SD have family history of striae distensae. 18 It was assumed that there were gene expression involvement in fibroblast metabolism that code elastin, collagen, and fibronectin was lower compared to normal skin. 19 There is no single therapy that is truly effective in treating striae distensae.…”
Section: Discussionmentioning
confidence: 99%
“…17 Gosh et al also showed than 73.3% subjects with SD have family history of striae distensae. 18 It was assumed that there were gene expression involvement in fibroblast metabolism that code elastin, collagen, and fibronectin was lower compared to normal skin. 19 There is no single therapy that is truly effective in treating striae distensae.…”
Section: Discussionmentioning
confidence: 99%